The effect of the detraining period caused by the COVID-19 pandemic on the change of direction performance of fencers - Kosova, S.; Koca Kosova, M. (Physical Education of Students, 2021)
Background and Study Aim The COVID-19 pandemic has caused many athletes to interrupt their regular training programme. The change-of-direction performance is a highly critical parameter for fencing. This study aims to investigate the effects of the detraining process caused by the COVID-19 pandemic on the change-of-direction performance of fencers. Material and Methods The study sample comprised 15 fencers (11 males, 4 females) who were competitors in the U17-20 age categories (mean age: 15.75±1.51 years; height: 170.30±7.68 cm; weight: 65.16±10.83 kg) in Turkey. All participants were high school students. Branch-specific change-of-direction tests (4-2-2-4-m shuttle and 7-m repeat lunge ability) were measured in the middle of the competition season and after the detraining period. The detraining period lasted 31 weeks due to the pandemic process. Results The results showed that participants were slower in the post 7-m repeat lunge ability test (23.32±2.21 sec.) compared with the pre-test (22.38±1.58 sec.) and participants were slower in the post 4-2-2-4-m shuttle test (6.43±0.54 sec.) compared with the pre-test (5.84±0.33 sec.) (p<0.05). Conclusions The present study showed that long-term detraining reduces fencer`s change-of-direction performance. Basic exercise programs can be arranged to reduce the rate of adverse effects during long-term detraining process.